Graziacrophyma gen. nov., a new genus of South American Acanthosomatidae (Hemiptera: Heteroptera) - Carvajal, Mariom A.; Faundez, Eduardo; Rider, David A. (My University, 2021)
Acrophyma Bergroth, 1916 is an acanthosomatid genus containing two species. Acrophyma cumingii (Westwood, 1837), which has an Andean distribution having been recorded from Chile and Argentina; and A. bicallosa (St?l, 1872) with a Neotropical distribution located in Brazil and Colombia (Fa?ndez, 2009; Morrone, 2001). The last contribution on this genus (Fa?ndez, 2009) clarified the taxonomic issues with A. cumingii. However, with additional material, we have realized the record provided in this previous work for A. bicallosa in Brazil corresponds to an undescribed species. Morphological differences and biogeographic relationships among A. cummingi and these two Neotropical species suggest the need for placing these last two species in their own new genus; which is the The genus Acrophyma Bergroth currently contains two species, the Andean A. cumingii (Westwood) and the Neotropical A. bicallosa (St?l). The examination of types and new material revealed that among the Neotropical species the Brazilian population differs from the Colombian, and the first one belongs to a new species in this group. A morphological analysis of the genus indicated the Neotropical species are different from the Andean species. According to the current most used generic characters in acanthosomatids, Neotropical species should be placed in a new genus. This is also supported by biogeographical relationships. New distributional records for the species of this group are provided.
Keywords: new genus; neotropical; new species; pentatomoidea